2015
DOI: 10.3892/mmr.2015.3297
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Bel-7402 human hepatoma cells induced by a ruthenium(II) complex coordinated by cordycepin through the p53 pathway

Abstract: A ruthenium(II) complex coordinated by cordycepin, [Cor‑Ru(II)], was synthesized for investigation as a potential novel candidate for cancer therapy. The antitumor activity of Cor‑Ru(II) was investigated by MTT and flow cytometry (FCM) assays. The results showed that Cor‑Ru(II) significantly inhibited the proliferation of Bel‑7402 human hepatoma cells and delayed cell cycle progression. Subsequent experiments using FCM and western blot analysis indicated that Cor‑Ru(II) induced cell apoptosis via suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, the activity of p53 is essential in suppressing tumors by different routes, such as inducing apoptosis and DNA repair and participating in cell cycle arrest. [41][42][43][44][45] Recent studies have suggested the involvement of NO in the suppression of p53 by reactive nitrogen species, which are produced from the reaction of NO with superoxide anion and other free radicals and nitration of tyrosine residues by the action of peroxynitrite generated from NO. Thus, the tyrosine residues are "nitro" group acceptors and they become 3-nitrotyrosine; this event can alter the structure and function of p53, reducing its activity and contributing to cancer development.…”
Section: No and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the activity of p53 is essential in suppressing tumors by different routes, such as inducing apoptosis and DNA repair and participating in cell cycle arrest. [41][42][43][44][45] Recent studies have suggested the involvement of NO in the suppression of p53 by reactive nitrogen species, which are produced from the reaction of NO with superoxide anion and other free radicals and nitration of tyrosine residues by the action of peroxynitrite generated from NO. Thus, the tyrosine residues are "nitro" group acceptors and they become 3-nitrotyrosine; this event can alter the structure and function of p53, reducing its activity and contributing to cancer development.…”
Section: No and Oxidative Stressmentioning
confidence: 99%
“…Therefore, the activity of p53 is essential in suppressing tumors by different routes, such as inducing apoptosis and DNA repair and participating in cell cycle arrest. 4145…”
Section: Introductionmentioning
confidence: 99%